The Effect of Corporate Social Responsibility on Organisational Commitment - Hodgkiss, Louise J (2009)
The business case for CSR has long been debated and researched, with inconsistent results. The impact of CSR on employee behaviour is one way in which CSR may improve businesses performance. Engendering organisational commitment from employees promises many benefits to businesses, including improved job performance and reduced employee turnover. Affective commitment, an emotional attachment to the organisation, is proposed to be the element of commitment that has the most influence on these positive outcomes, and is underpinned by social identification and social contract. Via the processes of social contract and social identification, employees’ perceptions of corporate social responsibility (CSR) are expected to increase their affective commitment, either through fulfilling a psychological contract with the organisation, or identifying with their goals and values. This will encourage them to remain a member of the organisation and act to uphold their side of the contract, bringing about the positive outcomes outlined above. This dissertation researches employees’ perceptions of CSR and affective commitment within Midlands Co-operative Society, a UK co-operative business with strong ethical values. The results showed that there was a significant positive relationship between primary stakeholder perception and affective commitment. Involvement in CSR activities was also found to be positively correlated to affective commitment. Recommendations for managers include increasing employee involvement in CSR activities, and improving their perceptions of the organisation’s CSR. These are both aimed at increasing employees’ affective commitment.